Crosstalk between vitamin status and Gut Microbiota: the key to maintaining immune homeostasis in the gut - Rakić, Marija; Repac, Jelena; Lunić, Tanja; Božić, Bojan; Božić-Nedeljković, Biljana (Archives of Pharmacy, 2023)
The human gut microbiota is a diverse ecosystem that harbours a variety of microorganisms, including proteobacteria, bacteria, viruses, fungi, protists, and archaea. These microorganisms are collectively involved in several vital functions, including nutrient metabolism, vitamin synthesis, immune system regulation, neurotransmitter production, drug metabolism, and communication with the central nervous system. Dysbiosis within the gut microbiota has been shown to be a critical factor in the development of chronic disease. Investigating the effects of gut microbiota composition on overall health holds promise for the treatment of inflammatory diseases and the development of new therapeutic interventions. One notable aspect of the functionality of the gut microbiota is its involvement in the production of essential B vitamins. These vitamins exert a significant influence on immune responses and the composition of the gut microbiota. Competition may occur between the host and the gut microbiota for B vitamins, which some bacteria obtain from food or from synthesis by other gut bacteria. Thus, the availability of B vitamins in the diet has the potential to influence the composition of the gut microbiota and thus immune homeostasis. The profile of the gut microbiota varies individually, with diet proving to be an important modulator of both its composition and functional properties. However, further extensive research efforts are needed to understand the complex interplay between the gut microbiota, vitamins, and immune response mechanisms. Such investigations have the potential to develop innovative therapeutic strategies for a spectrum of inflammatory diseases, opening new avenues for improved patient outcomes.